EXPLORATION OF FINANCIAL LITERACY STRATEGIES AND ADOPTION OF FINANCIAL TECHNOLOGY TO SUPPORT SMALL AND MEDIUM ENTERPRISES GROWTH IN BORDER AREAS : A CASE STUDY IN BENGKAYANG - Rissa Ayustia; Jones Parlindungan Nadapdap; Jorge Ribeiro Freitas; Rismanto Gatot Trisilo; Eligia Monixa Salfarini (Jurnal Ekonomi, 2023)
This case study examines how financial technology adoption and financial literacy initiatives support the expansion of small and medium-sized enterprises (SMEs) in border regions, with a particular emphasis on Bengkayang. Businesses face special opportunities and problems due to the border location, which calls for a customized strategy to technology integration and financial management. The research examines internal strengths and weaknesses as well as external opportunities and threats pertinent to the SME's goals using Internal Factors Analysis Strategy (IFAS) and External Factors Analysis Summary (EFAS) matrix. The IFAS analysis highlights significant advantages in the form of rising government backing and interest, offset by obstacles in the form of resistance and difficulty gaining access to technology. Opportunities like growing demand and partnerships are identified by the EFAS research, along with concerns like political instability and competition. Combining these results, the report suggests proactive risk mitigation, diversified financial services, enhanced collaborations, integrated technology access initiatives, and personalized financial literacy programs. In the particular setting of Bengkayang, a methodical approach to impact evaluation and ongoing monitoring and modification is suggested to guarantee the efficacy of initiatives in fostering SME growth.